Effect of Multiple Transcranial Direct Current Stimulation Sessions on Cognitive Function in Parkinson’s Disease: A Systematic Review - Martalia, Violine; Fakhri, Aldithya; Andini, Dheanita Nissrina; Gabrian, Arden; Gabrielle, Aileen; Lestari, Yohana Eka Trisnawawti; Prawiroharjo, Pukovisa (Acta Neurologica Indonesia, 2026)
Background: Cognitive impairment is a common non-motor symptom of Parkinson’s disease (PD) that significantly affects quality of life. Transcranial direct current stimulation (tDCS), a non-invasive neuromodulation technique, has been proposed to enhance cognitive function in PD. This study systematically reviews the effects of multiple tDCS sessions on cognitive outcomes in PD patients. Methods: A systematic search of PubMed, Cochrane, ScienceDirect, and Medline was conducted in accordance with PRISMA guidelines. Randomized controlled trials (RCTs) assessing the impact of tDCS on cognitive function in PD were included. Study quality was evaluated using the RoB 2 tool. Results: Three RCTs using anodal tDCS over the dorsolateral prefrontal cortex (DLPFC) for 20–25 minutes per session were included. Two studies reported improvements in executive function, attention, memory, and language, with some effects maintained at 3-month follow-up. One study found delayed improvements at 1-month follow-up. However, findings were mixed across studies, especially for memory, language, visuospatial abilities, and global cognition. All studies reported that tDCS was safe and well-tolerated, with only mild, transient side effects. Discussion: Anodal tDCS may enhance specific cognitive functions, particularly executive function and attention, in PD. However, inconsistent findings across studies likely reflect differences in stimulation protocols and outcome measures. Conclusion: While tDCS is a safe intervention, its cognitive efficacy in PD remains uncertain. Methodological variability across studies limits generalizability. Further large-scale RCTs using standardized protocols, consistent cognitive measures, and extended follow-up are needed to clarify the role of tDCS in cognitive rehabilitation for PD.